ASSESSMENT OF SUPERVISION PROBLEMS FACED BY POSTGRADUATE GIRLS STUDENTS DURINGRESEARCH: A COMPARATIVE ANALYSIS OF JAMSHORO UNIVERSITIES - Channar, Sheeba Hussain; Junejo, Dahshilla; Khaskhely, Mahvish Kanwal; Baladi, Nazish (International Journal of Psychosocial Rehabilitation, 2020)
Jamshoro is fundamentally an educational city located near Hyderabad, Jamshoro district. It is renowned for three universities. Students come to study here across the country. There are many problems dealt by the students at various educational stages such as “insufficient support of administration”, “data collection problems” and “male dominance problems”. This study focuses on supervision problems faced by postgraduate girls students. The data was compiled from three universities namely University of Sindh (UoS),Mehran University of Engineering Technology (MUET) and Liaquat University of Medical and Health Science (LUMHS). The sample size of this study is 300 post graduate girls students from each university. The data of this paper was collected through self-administrated questionnaires. The data was analyzed using various tools in the SPSS; the tools are cluster bar charts and pie charts. The result of this study reveals that postgraduate girl students have been facing lack of assistance by supervisor, lack experience in supervisory responsibility and provision of little support in finding the relevant literature and methodologies by the supervisor. Conclusion of paper shows that the Sindh university postgraduate girl students face more problems in terms of supervisors as compared to MUET and then LUMHS.